Risk reduction through acquisitions: The roles of firm-specific investments and agency hazards - WANG, Heli (Institutional Knowledge at Singapore Management University, 2006)
This paper provides a stakeholder-based rationale for firm risk reduction through diversification. While firm-specific investments from stakeholders are often important sources of firm competitive advantage and economic rents, there is a reduced incentive for stakeholders to make these investments due to the risk associated with firm-specific investments. Since the risk associated with firm-specific investments is often related to the total firm risk level, we argue that stakeholders’ difficulties in diversifying the risks associated with their firm-specific investments create incentives for risk management by firms. We test this argument in a diversification setting. Based on a sample of firms’ first acquisition moves, we find that firms are more likely to engage in risk reduction through diversification when high levels of firm-specific assets are important to the firm's operations. Several proxies for stakeholders’ specific investments are found to be significant in explaining cross-sectional variation in the extent of ex ante risk reduction in acquisitions.